Lichenoid drug eruption induced by colchicine: case report. (3rd April 2017) - An, Isa; Demir, Vasfiye; Akdeniz, Sedat
Abstract: Lichenoid drug eruption (LDE) is a common cutaneous side effect of drugs including antimalarials, antihypertensives, nonsteroids, anti-inflammatory drugs and diuretics. The physiopathologic relationship between colchicine treatment and LDE is unclear. There is very little documentation of LDE induced by colchicine in the literature. In this report, we present a case that developed LDE on the abdomen and the legs during the colchicine treatment.